2016
DOI: 10.1039/c6cp06528g
|View full text |Cite
|
Sign up to set email alerts
|

Trapped in the coordination sphere: nitrate ion transfer driven by the cerium(iii/iv) redox couple

Abstract: Redox-driven ion transfer between phases underpins many biological and technological processes, including industrial separation of ions. Here we investigate the electrochemical transfer of nitrate anions between oil and water phases, driven by the reduction and oxidation of cerium coordination complexes in oil phases. We find that the coordination environment around the cerium cation has a pronounced impact on the overall redox potential, particularly with regard to the number of coordinated nitrate anions. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…[8,9] Beyond its practical end-usage, the ability to easily cycle between the + 3 and + 4 oxidation states leads to the use of Ce as a proxy element in studies of valence-controlled solvent extraction separation of trivalent and tetravalent actinides and lanthanides in the PUREX (Plutonium Uranium Reduction EXtraction) process for nuclear fuel reprocessing. [3,[6][7][8]10] Solvent extraction processes for Ce IV recovery using solvating extractants such as tributylphosphate (TBP) or diglycolamides in organic diluents are unstable at high acid or metal loading, manifested by the splitting of the organic phase into a dense metal/acid-rich phase and a light diluent phase. Thirdphase formation is triggered by the polar solute-induced aggregation of the amphiphilic ligand upon extraction into the organic phase and the eventual coalescence of reverse micellar aggregates into larger-scale assemblies, resulting in a failure of the extraction process, and places an upper boundary on the applicable metal concentration in the feed solution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[8,9] Beyond its practical end-usage, the ability to easily cycle between the + 3 and + 4 oxidation states leads to the use of Ce as a proxy element in studies of valence-controlled solvent extraction separation of trivalent and tetravalent actinides and lanthanides in the PUREX (Plutonium Uranium Reduction EXtraction) process for nuclear fuel reprocessing. [3,[6][7][8]10] Solvent extraction processes for Ce IV recovery using solvating extractants such as tributylphosphate (TBP) or diglycolamides in organic diluents are unstable at high acid or metal loading, manifested by the splitting of the organic phase into a dense metal/acid-rich phase and a light diluent phase. Thirdphase formation is triggered by the polar solute-induced aggregation of the amphiphilic ligand upon extraction into the organic phase and the eventual coalescence of reverse micellar aggregates into larger-scale assemblies, resulting in a failure of the extraction process, and places an upper boundary on the applicable metal concentration in the feed solution.…”
Section: Introductionmentioning
confidence: 99%
“…Although rare earth elements (REEs) are characterized by similar physico‐chemical properties, certain lanthanides have accessible redox transitions permitting their separation from the other REEs in their +3‐oxidation state [1] . Examples include the reduction and precipitation of europium(II) sulfate [2] or the oxidation of cerium(IV) followed by its solvent extraction separation [3–7] . Cerium(IV) oxide, or ceria, is an industrially important material with applications in glass polishing, organic catalysis, environmental remediation, solid‐oxide fuel cells, and as possible partial replacement for neodymium in NdFeB magnets [8,9] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has focused on investigating Ln coordination in TODGA systems from extraction from high HNO 3 concentrations. Under these conditions, multiple spectroscopic techniques have been utilized [i.e., extended X-ray absorption fine structure, Fourier transform infrared (FT-IR), and time-resolved laser-induced fluorescence spectroscopy (TRLIFS)] in tandem with distribution ratio extractant dependence to determine Ln coordination in nonpolar paraffinic organic phases. , These studies demonstrated that Ln are extracted by TODGA in a cationic, trischelate homoleptic complex, [Ln­(TODGA) 3 ] 3+ , with outer-sphere NO 3 – located in the clefts between TODGA alkyl tails . Sasaki et al proposed that extraction of significant amounts of HNO 3 along with the Ln facilitates formation of the 1:3 [Ln­(TODGA) 3 ] 3+ complex .…”
mentioning
confidence: 99%